Analisa Pengaruh Heat Treatment Terhadap Nilai Kekerasan Expeller Arm Digester di PT. Hindoli Mill Sungai Lilin - Emilia Mianti; Fenoria Putri; Soegeng Witjahjo (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
This study investigated the effect of varying heat treatment on the hardness of expeller arm digesters. Wear is a surface failure that can alter the surface profile and affect the performance of components. This is due to the release of particles from the surface of the material and the low hardness of the Expeller Arm Digester which is made from low carbon steel with a carbon content of 0.189%. One method of increasing its hardness is through heat treatment in the form of a hardening process. The study investigated hardening using different holding times (25, 30 and 35 minutes) and cooling media (water, brine and oil). Vickers hardness tests were then carried out on both the original expeller arm digester samples and the treated samples. The best results were obtained with a 35 minute holding time and water cooling, giving a hardness of 548.12 VHN and an influence percentage of 99.45%. The lowest hardness of 276.76 VHN and 0.7% influence percentage was observed with a holding time of 35 minutes and oil cooling. The microstructure affects the hardness of the steel, the steel with a higher martensite content will cause an increase in the hardness of the steel.